Interaction of a cold cloud with a hot wind: the regimes of cloud growth and destruction and the impact of magnetic fields. Issue 3 (14th October 2020) - Sparre, Martin; Pfrommer, Christoph; Ehlert, Kristian
ABSTRACT: Multiphase galaxy winds, the accretion of cold gas through galaxy haloes, and gas stripping from jellyfish galaxies are examples of interactions between cold and hot gaseous phases. There are two important regimes in such systems. A sufficiently small cold cloud is destroyed by the hot wind as a result of Kelvin–Helmholtz instabilities, which shatter the cloud into small pieces that eventually mix and dissolve in the hot wind. In contrast, stripped cold gas from a large cloud mixes with the hot wind to intermediate temperatures, and then becomes thermally unstable and cools, causing a net accretion of hot gas to the cold tail. Using the magneto-hydrodynamical code arepo, we perform cloud crushing simulations and test analytical criteria for the transition between the growth and destruction regimes to clarify a current debate in the literature. We find that the hot-wind cooling time sets the transition radius and not the cooling time of the mixed phase. Magnetic fields modify the wind–cloud interaction. Draping of wind magnetic field enhances the field upstream of the cloud, and fluid instabilities are suppressed by a turbulently magnetized wind beyond what is seen for a wind with a uniform magnetic field. We furthermore predict jellyfish galaxies to have ordered magnetic fields aligned with their tails. We finally discuss how the results of idealized simulations can be used to provide input to subgrid models in cosmological (magneto-)hydrodynamical simulations, which cannot resolve the detailed small-scale structure of cold gas clouds in the circumgalactic medium.